Functional Diversity of p53 in Human and Wild Animals - Li, Yi; Zhang, Meng-Chen; Xu, Xiao-Kang; Zhao, Yang; Mahanand, Chatoo; Zhu, Tao; Deng, Hong; Nevo, Eviatar; Du, Ji-Zeng; Chen, Xue-Qun (Frontiers in Endocrinology, 2019)
The common understanding of p53 function is a genome guardian, which is activated by diverse stresses stimuli and mediates DNA repair, apoptosis and cell cycle arrest. Increasing evidence has demonstrated p53 new cellular functions involved in abundant endocrine and metabolic response for maintaining homeostasis. However, TP53 is frequently mutant in human cancers, and the mutant p53 (Mut-p53) turns to an “evil” cancer-assistant. Mut-p53-induced epithelial-mesenchymal transition (EMT) plays a crucial role in the invasion and metastasis of endocrine carcinomas, and Mut-p53 is involved in cancer immune evasion by upregulating PD-L1 expression. Therefore, Mut-p53 is a valuable treatment target for malignant tumors. Targeting Mut-p53 in correcting sequence and conformation are increasingly concerned. Interestingly, in wild animals, p53 variations contribute to cancer resistant and high longevity. This review has discussed the multiple functions of p53 in health, diseases and nature evolution, summarized the frequently mutant sites of p53, and the mechanisms of Mut-p53-mediated metastasis and immune evasion in endocrine cancers. We have provided a new insight for multiple roles of p53 in human and wild animals.